High power gaas/algaas mode-locked lasers - Tandoi, G.; Ironside, Charlie; Bryce, A.; McDougall, S. (2009)
This work shows preliminary results from Colliding-Pulse Mode-Locked lasers in a GaAs/AlGaAs highpower material structure, where COMD limits the output power to 40mW. Results of gain and absorption spectra, measured to model the mode-locking operation of the devices, are also presented. ©2009 IEEE.